Distribution Patterns of Tuberculosis in South Sumatra: A Descriptive Analysis from 2019 to 2023 - Devi Savitri Effendy; Sri Ramdayani Apdi; Syahlani; Sumarniyati; Reva Muftira Jamil (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Indonesia is one of the countries with the highest rate of tuberculosis burden in the world, ranking second globally. Pulmonary tuberculosis is one of the global health problems that can have a major impact on quality of life, with higher mortality rates and lower recovery rates due to poorer medication adherence. Objective: This study aims to describe the distribution of tuberculosis cases in the South Sumatra Province area during the 2019–2023 period based on secondary data from the South Sumatra Provincial Health Profile. Methods: This study used a quantitative descriptive approach by analyzing secondary data sourced from the South Sumatra Provincial Health Profile document. Data is analyzed in the form of graphs and tables and described narratively to identify patterns and trends of cases. Results: Tuberculosis cases are flaxative from year to year. A decrease in cases was recorded in certain years, but some indicators such as maternal mortality remained high. Geographical factors, limited health facilities, and socio-cultural factors are expected to be the main contributors to this trend. Conclusion: The distribution of tuberculosis cases in South Sumatra is influenced by several factors and shows the need to increase control efforts evenly throughout the region.